Who's watching? The market for prostitution services - Marina Della Giusta; Maria Laura Di Tommaso; Steinar Strøm (University of Oslo, Department of Economics, 2005)
This paper presents an economic model of prostitution, which differs from the existing literature in that it makes no restrictive assumptions regarding the gender, pay, and nature of forgone earning opportunities of prostitutes and clients, and applies the same behavioural hypotheses to both. Our model gives a central role to stigma and reputation effects for both clients and prostitutes. We discuss demand, supply, and equilibrium results, indicating the possible effects of different policies on the industry and its different markets.
Keywords: J16; J22; J23; J24; 330; Prostitution; Gender; Labour supply and demand; Reputation; Prostitution; Reputation; Arbeitsangebot; Arbeitsnachfrage; Theorie